Heterogeneous FASnI3 Absorber with Enhanced Electric Field for High-Performance Lead-Free Perovskite Solar Cells - Wu, Tianhao; Liu, Xiao; Luo, Xinhui; Segawa, Hiroshi; Tong, Guoqing; Zhang, Yiqiang; Ono, Luis K.; Qi, Yabing; Han, Liyuan (Nano-micro letters, 2022)
Highlights A novel strategy to further improve the efficiency of lead-free tin perovskite solar cells by carefully controlling the built-in electric field in the absorber is described. A promising efficiency of 13.82% was obtained based on the formamidinium tin iodide (FASnI 3 ) perovskite solar cells with a vertical Sn 2+ gradient and an enhanced electric field. The solar cell with a heterogeneous FASnI 3 absorber is ultrastable, maintaining over 13% efficiency after operation under 1-sun illumination for 1,000 h in air. Lead-free tin perovskite solar cells (PSCs) have undergone rapid development in recent years and are regarded as a promising eco-friendly photovoltaic technology. However, a strategy to suppress charge recombination via a built-in electric field inside a tin perovskite crystal is still lacking. In the present study, a formamidinium tin iodide (FASnI 3 ) perovskite absorber with a vertical Sn 2+ gradient was fabricated using a Lewis base-assisted recrystallization method to enhance the built-in electric field and minimize the bulk recombination loss inside the tin perovskites. Depth-dependent X-ray photoelectron spectroscopy revealed that the Fermi level upshifts with an increase in Sn 2+ content from the bottom to the top in this heterogeneous FASnI 3 film, which generates an additional electric field to prevent the trapping of photo-induced electrons and holes. Consequently, the Sn 2+ -gradient FASnI 3 absorber exhibits a promising efficiency of 13.82% for inverted tin PSCs with an open-circuit voltage increase of 130 mV, and the optimized cell maintains over 13% efficiency after continuous operation under 1-sun illumination for 1,000 h.